2022
DOI: 10.1155/2022/2500594
|View full text |Cite
|
Sign up to set email alerts
|

Differences of Clinicopathological Features between Metaplastic Breast Carcinoma and Nonspecific Invasive Breast Carcinoma and Prognostic Profile of Metaplastic Breast Carcinoma

Abstract: Introduction. Metaplastic breast carcinoma is a rare special type of breast cancer, which has distinguished clinical characteristics. We aimed to evaluate the clinicopathological features of metaplastic breast carcinoma compared with nonspecific invasive breast carcinoma and study the prognosis of metaplastic breast carcinoma. Methods. We reviewed metaplastic breast carcinoma cases (n = 37) from January 2000 to December 2021 and nonspecific invasive breast carcinoma cases (n = 433) from January 2019 to Decembe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…The research on the factors related to the prognosis of various diseases is the current research focus (36)(37)(38)(39). It is suggested that Dabuyin pill can inhibit the development of secondary sexual characteristics, reduce the volume of the uterus and ovaries, slow down the speed of bone maturation, and has no adverse reactions.…”
Section: Discussionmentioning
confidence: 99%
“…The research on the factors related to the prognosis of various diseases is the current research focus (36)(37)(38)(39). It is suggested that Dabuyin pill can inhibit the development of secondary sexual characteristics, reduce the volume of the uterus and ovaries, slow down the speed of bone maturation, and has no adverse reactions.…”
Section: Discussionmentioning
confidence: 99%
“…The research on the prognosis and related biological indicators of different diseases is the focus of current research (26)(27)(28)(29)(30). The parameters of breast dynamic enhancement MRI in young breast cancer patients are specific, which is manifested by an increased proportion of patients with non-mass enhancement, a decrease in the ADC, and is related to the clinical features and prognosis of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Prognosis and related indicators of different diseases are the focus of current research (26)(27)(28)(29). Our model could accurately identify high risk of death within 5 years of surgery in non-small cell lung cancer patients.…”
Section: Discussionmentioning
confidence: 99%